La psichiatria come psicoterapia - Fagioli, Massimo (Il sogno della farfalla, 2013)
This unpublished text by Massimo Fagioli dates back to the summer of 2004, and deals with the indissoluble link between psychiatry ad psychotherapy, to the point of having to affirm that one does not exist without the other. Fagioli clarifies the fundamental terms of psychotherapy, which are setting, transference, interpretation; talks about his particular group setting, the Collective Analysis which has been operating for 40 years; reaffirms his method based on a fusion between theory and practice; defines fundamental concepts like image, instinct, drive, dwelling, in particular, on the existing confusion that surrounds words like negation and desire.